Bioremediation of oil from domestic wastewater using mixed culture : effects of inoculum concentration and agitation speed - Mohd Khairul Nizam, Mohd Zuhan (2008)
The volume of oil in domestic wastewater is increasing each year due to the urbanization and industrial development all around the world. It is concerned that the increasing of oil in the wastewater could cause severe impact to the environment and to human health. Bioremediation of oil from domestic wastewater using mixed culture is being studied to overcome this problem. Microorganisms from local palm oil plant are utilised for this study. The ability of the microorganisms to degrade the oil is observed by investigating effect of concentration of the inoculum (g/ml) and the agitation speed (rpm) on oil removal. The optimum condition for these microorganisms to degrade oil is aimed for the highest volume of oil degraded. From the result obtained it is show that agitation with the speed of 150 rpm give the best condition for oil removal while the addition of 4g/110ml of inoculum concentration over wastewater and oil volume give the optimum oil removal. Higher concentration of inoculum cause high oil removal but at highly concentrated inoculum could cause reverse effect. Therefore high agitation also contributes to higher oil removal.